Effect of Temperature and Pressure Variation on CO₂ Methanation Performance in a PFR Reactor Using Ni/Al₂O₃ Catalyst - Adinda Anandyta Arifa; Angelica Ruth Clara Sirait; Saskia Syifa Nurqolbi; Silviyana Rahma Qurrota Ayun; Yusup Abdillah Dinata; Mutiara Sahita Dwi Azzahra (Journal of Chemical Engineering Research Progress, 2026)
This study investigates the effect of feed temperature and pressure on the performance of CO₂ methanation using simulation results from Aspen HYSYS. The analysis focuses on the variation of CO and CH₄ mole fractions in the product stream under temperature ranges of 350–500 °C and pressure ranges of 100–300 kPa. The results show that temperature has a minimal effect on both CO and CH₄ compositions, with only slight fluctuations observed, indicating that the system operates equilibrium conditions. In contrast, pressure exhibits a more noticeable influence, where increasing pressure leads to a gradual decrease in CO mole fraction and a corresponding increase in CH₄ mole fraction. These findings are consistent with the exothermic nature of the methanation reaction and Le Chatelier’s principle, confirming that higher pressure favors methane formation. Overall, the study highlights that pressure is a more significant operating parameter than temperature in enhancing CO₂ conversion to CH₄ under the investigated conditions. Copyright © 2026 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).